Production of silica gel from Tunisian sands and its adsorptive properties. (June 2017) - Lazaar, K.; Hajjaji, W.; Pullar, R.C.; Labrincha, J.A.; Rocha, F.; Jamoussi, F.
Abstract: Thanks to its highly absorbent character, silica gel is used in several applications, such as air moisture removal, as a treatment agent for effluents. In this study, silica gels were synthesised from Tunisian sands, collected from the Fortuna and Sidi Aich Formations in northern and central Tunisia. The collected quartz sand raw materials, as well as the prepared silica gels, were characterised by different techniques, such as X-ray diffraction (XRD), X-ray fluorescence (XRF) and scanning electron microscopy (SEM). XRD patterns of quartz sands showed quartz as main phase (86.1–98%), with lower contents of potassic feldspars, along with kaolinite and calcite. These quartz sands presented relatively small quantities of Fe2 O3 (0.3%–0.5%) and TiO2 (0.1%–0.6%). The synthesised silica gels exhibited pore diameters exceeding 20 Å and surface areas up to 194 m 2 /g, comparable with those described in the literature and commercial silica gel. N2 adsorption isotherms showed that the silica gels prepared from Tunisian sands are mesoporous materials with high adsorption capacities. To understand better their adsorbent properties and applicability on an industrial scale, these gels were tested for methylene blue (MB) absorption. Maximum decolourisation rates (up to 96% after a contact time of 180 min) occurred with products synthesised at pH 3. The adsorption mechanism fitted better with a Langmuir model, revealing a monolayer coverage process of MB molecules over the gel surface, and the adsorption kinetics of the dye on these materials is well described by the second order model. The corresponding equilibrium adsorption capacities obtained from experimental data (Qexp  = 292–214 mg/g) were close to the estimated maximum adsorption capacities (Qe  = 333–250 mg/g), and to that of an industrial silica gel (250 mg/g). Highlights: The silica gels were synthesised from Fortuna and Sidi Aich Tunisian sands. These quartz sands presented relatively small quantities of Fe2 O3 and TiO2 . Obtained silica gels exhibited surface areas comparable to tested commercial one. Maximum MB decolourisation rates occurred in products synthesised at pH 3.